Abstract 104: Fetal Posterior Cerebral Artery (PCA) Occlusion from Occluded Cavernous ICA Stent - Aydan Kahriman; William Borchert; Adam Blenden; Hesham Masoud (Stroke: Vascular and Interventional Neurology)
Introduction Posterior Cerebral Artery (PCA) is a medium vessel occlusion (MVO) which is 5‐10% of all acute ischemic events. Safety and efficacy of mechanical thrombectomy in posterior circulation MVO is unclear compared to medical treatment only (1). There is concern that fragility of distal, smaller vessels may have an increased risk of procedural complications (e.g., arterial dissection and or perforations). More people are getting flow divertors over the years and rate of flow diverter of ICA occlusion is 0.05%‐0.08% (2). Here we present a case of embolic fetal PCA stroke with ICA stent occlusion. Methods We report a case of fetal origin posterior cerebral artery occlusion from ICA with literature search of Pubmed. Results 77 years old female with left cavernous‐ICA stent presented from a rehab facility with complaints of word finding difficulty, confusion, right hemiparesis, right sided neglect, and visual disturbance. In the emergency department (ED), her NIHSS was 28. ED presentation was 2.5 hrs after the last known well (LKW). Of note, patient had a with left cavernous‐ICA stent placement a month before the presentation and was noncompliant to antiplatelets. CT head was negative for intracranial bleeding and ASPECT score was 7. CT angiography head and neck was obtained, showing new complete interval occlusion of the intracranial extradural left ICA with reconstitution of distal branches through anterior communicating artery. Patient received IV thrombolytics, intubated for airway protection and was transferred to a comprehensive stroke center for possible mechanical thrombectomy. Time of the arrival was approximately 6 hours after the LKW, reexamination was hindered by the sedation and intubation but was concerning for possible PCA occlusion rather than ICA occlusion. As the localization of ischemic area was unclear, CT perfusion (CTP) was obtained. CTP showed 27 ml penumbra without core infarct in left PCA territory. As fetal origin of left PCA from ICA is occluded, without ability to access through occluded stent, noted risk of left ICA complications with attempts to recanalize stent for noted PCA hypoperfusion outweigh the benefits. With the exam improvement post thrombolytics administration and small penumbra, mechanical thrombectomy was not indicated. Conclusion In acute large vessel occlusion, utility of CT perfusion (CTP) usually recommended after 6 hours from last well known. In this case, patient presented within the 6 hours but the reexamination post thrombolytics was not localizing to suggest large vessel occlusion (LVO) and the territory at risk was unclear. We described a left intracranial ICA flow diversion occlusion without anterior circulation ischemia and left PCA ischemia demonstrated. In this case, CTP was employed to differentiate the territory at risk for triage to appropriate intervention, to differentiate the LVO vs MVO.